Language Engineering and Rigorous Software Development International LerNet ALFA Summer School 2008, Piriapolis, Uruguay, February 24 - March 1, 2008, Revised, Selected Papers - Bove, Ana; Barbosa, Luis Soares; Pardo, Alberto; Pinto, Jorge Sousa (Programming and Software Engineering,, 2009)
This book constitutes the thoroughly refereed revised tutorial lectures of the International LerNet ALFA Summer School on Language Engineering and Rigorous Software Development, held in Piriapolis, Uruguay, in February/March 2008. The volume presents three courses on type theory: an introductory tutorial, a course on type-based termination, and a practical introduction to dependent types. A case study of a static analyzer based on abstract interpretation, a tutorial on combinator parsing, and a study of extended static checking using a point-free transform completes the volume. Together these contributions will be an invaluable tool for graduate students and researchers looking forward to keeping up to date with the latest developments in rigorous approaches to software development.